2021
DOI: 10.3390/ijms22031178
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Flavodiiron Proteins Flv2-Flv4 in Chloroplasts of Arabidopsis and Tobacco Plants Provides Multiple Stress Tolerance

Abstract: With the notable exception of angiosperms, all phototrophs contain different sets of flavodiiron proteins that help to relieve the excess of excitation energy on the photosynthetic electron transport chain during adverse environmental conditions, presumably by reducing oxygen directly to water. Among them, the Flv2-Flv4 dimer is only found in β-cyanobacteria and induced by high light, supporting a role in stress protection. The possibility of a similar protective function in plants was assayed by expressing Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The heterodimer Flv1/3 is conserved in all cyanobacteria and is responsible for oxygen photoreduction downstream of PSI in a Mehler-like reaction that does not produce ROS (Allahverdiyeva et al, 2013), whereas the heterodimer Flv2/4 is only present in β-cyanobacteria and was reported to be involved in photoprotection of both PSII and PSI (Zhang et al, 2009(Zhang et al, , 2012Bersanini et al, 2014Bersanini et al, , 2017Chukhutsina et al, 2015;Santana-Sanchez et al, 2019). In angiosperms, in which FDPs are absent, introduction of two FDPs could therefore possibly replace Tognetti et al, 2006Tognetti et al, , 2007aTognetti et al, , 2007bZurbriggen et al, 2008;Shvaleva et al, 2009;Coba de la Peña et al 2010;Giró et al, 2011;Ceccoli et al, 2012;Lodeyro et al, 2012;Gharechahi et al, 2015;Mayta et al, 2018;Gómez et al, 2020;Niazian et al, 2021 Overexpression of cyanobacterial and moss FDPs AET Arabidopsis, tobacco, barley, rice Yes Drought/ fluctuating light stress Yamamoto et al, 2016;Gómez et al, 2018;Wada et al, 2018;Tula et al, 2020;Shahinnia et al, 2021;Vicino et al, 2021 Abbreviations: AET, alternative electron transfer; ATP, adenosine triphosphate; LHC, light-harvesting complex; NPQ, nonphotochemical quenching.…”
Section: Increasing Electron Transport Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…The heterodimer Flv1/3 is conserved in all cyanobacteria and is responsible for oxygen photoreduction downstream of PSI in a Mehler-like reaction that does not produce ROS (Allahverdiyeva et al, 2013), whereas the heterodimer Flv2/4 is only present in β-cyanobacteria and was reported to be involved in photoprotection of both PSII and PSI (Zhang et al, 2009(Zhang et al, , 2012Bersanini et al, 2014Bersanini et al, , 2017Chukhutsina et al, 2015;Santana-Sanchez et al, 2019). In angiosperms, in which FDPs are absent, introduction of two FDPs could therefore possibly replace Tognetti et al, 2006Tognetti et al, , 2007aTognetti et al, , 2007bZurbriggen et al, 2008;Shvaleva et al, 2009;Coba de la Peña et al 2010;Giró et al, 2011;Ceccoli et al, 2012;Lodeyro et al, 2012;Gharechahi et al, 2015;Mayta et al, 2018;Gómez et al, 2020;Niazian et al, 2021 Overexpression of cyanobacterial and moss FDPs AET Arabidopsis, tobacco, barley, rice Yes Drought/ fluctuating light stress Yamamoto et al, 2016;Gómez et al, 2018;Wada et al, 2018;Tula et al, 2020;Shahinnia et al, 2021;Vicino et al, 2021 Abbreviations: AET, alternative electron transfer; ATP, adenosine triphosphate; LHC, light-harvesting complex; NPQ, nonphotochemical quenching.…”
Section: Increasing Electron Transport Capacitymentioning
confidence: 99%
“…In angiosperms, in which FDPs are absent, introduction of two FDPs could therefore possibly replace several ROS scavenging enzymes and reactions, thus saving energy and nitrogen sources or adding extra protection. Indeed, transgenic lines of tobacco, Arabidopsis and barley expressing cyanobacterial Flv1/3 or Flv2/4 proteins in chloroplasts showed that FDPs are able to act as additional electron sinks in plants as well, particularly under stress conditions, such as drought and fluctuating light stress, thereby improving photosynthetic performance (Gómez et al, 2018; Tula et al, 2020; Shahinnia et al, 2021; Vicino et al, 2021). In other instances, two FDPs from the moss Physcomitrella patens were introduced into Arabidopsis and rice, revealing similar effects of FDPs and CET in maintaining the pmf under unfavorable growth conditions (Yamamoto et al, 2016; Wada et al, 2018).…”
Section: Improving Crop Yields Through Optimization Of Photosynthetic...mentioning
confidence: 99%
“…We tested this possibility by expressing Synechocystis Flv2/Flv4 in chloroplasts of tobacco and Arabidopsis (Figure 1). Flv-expressing plants exhibited increased tolerance toward various stresses including drought, as reflected by better growth and preservation of photosynthetic activity and membrane integrity [84]. Metabolic profiling under drought showed enhanced accumulation of soluble sugars and amino acids in transgenic Arabidopsis and a remarkable shift of sucrose into starch, in line with the metabolic responses of drought-tolerant genotypes [84].…”
Section: Flavodi-iron Proteins Act As Electron Sinks and Enhance Plan...mentioning
confidence: 98%
“…Flv-expressing plants exhibited increased tolerance toward various stresses including drought, as reflected by better growth and preservation of photosynthetic activity and membrane integrity [84]. Metabolic profiling under drought showed enhanced accumulation of soluble sugars and amino acids in transgenic Arabidopsis and a remarkable shift of sucrose into starch, in line with the metabolic responses of drought-tolerant genotypes [84]. The results indicate that the Flv2/Flv4 complex retained its stress-protective activities when expressed in chloroplasts of angiosperms by acting as an additional electron sink through functional interaction with the chloroplast PETC, despite the evolutionary divergence between cyanobacteria and angiosperms.…”
Section: Flavodi-iron Proteins Act As Electron Sinks and Enhance Plan...mentioning
confidence: 99%
“…A Caffeoyl-CoA O-methyltransferase gene conferred drought tolerance by promoting lignin synthesis [ 99 ]. The expression of flavodiiron proteins/reductases genes Flv2 , Flv 3 , and Flv4 in Arabidopsis and tobacco plants enhanced the drought tolerance [ 100 ].…”
Section: Genes Related To Drought Tolerancementioning
confidence: 99%